Study on the seismic lethal level of buildings and seismic disaster risk in Guangzhou, China. Issue 1 (31st December 2022) - Xia, Chaoxu; Nie, Gaozhong; Li, Huayue; Fan, Xiwei; Yang, Rui
Abstract: Seismic disaster risk assessment results are an important way to reduce disaster losses and casualties. In this article, a seismic disaster risk assessment method is constructed based on the lethal level, and a quantitative assessment of the earthquake disaster risk in Guangzhou is carried out. There are four typical building types in this study area: brick-wood structures, brick-concrete structures, reinforced concrete structures, and civil structures. Typical building structural components (vertical load-bearing component, ring beam, mortar of infilled wall, roof or floor structure, foundation, height of building, nonstructural component, anti-seismic joint or other anti-seismic measures) are selected to build the lethal level index system of buildings. On the basis of the field survey, a lethal level of 431 survey points is obtained. The average lethal level in urban areas is 0.3476, and in rural areas is 0.4198, the overall lethal level of each township is 0.389, and the errors between the urban and rural areas are 0.0414 and 0.0308, and the fitting results coefficient of determination (R 2 ) values are 0.6803 and 0.6714, respectively, the results is good. Furthermore, considering the seismic hazard (peak ground acceleration, PGA), population exposure and lethal level, the seismic disaster risk distribution of the Guangzhou area is determined. Under different intensities, the risk of death has shown obvious characteristics, as the intensity increases, the number of possible deaths increases rapidly, ranging from a few to several thousand, the higher risk areas are relatively fixed, generally mainly located in the central city, the quantitative assessment results of disaster risk also have obvious directivity. The areas with the highest risk are located in most areas of Tianhe District, Liwan District and Haizhu District, the highest grid death result is more than 1; the lethal level of Baiyun District and Huangpu District is low, but the death risk is also higher, generally between 0.5 and 1, in rural areas in the southern and northern regions of Guangzhou, the risk is relatively low, generally between 0 and 0.5. The distribution map of seismic disaster risk can provide solid scientific and technological support for the government to investigate potential risk points.